Peningkatan Semangat Berwirausaha Pada Paguyuban Umkm “Aku Bisa” Di Kota Semarang - Yani, Tri Endang Yani; Wibisono, Totok Wibisono; Roestanto, Anantya Roestanto; Sujito, Sujito (Universitas Sahid Surakarta, 2024)
Abstract: In Krobokan Village, West Semarang, there is a Micro, Small and Medium Enterprises Association (MSMEs)”AKU BISA”. This asssociation accommodates approximately 50 MSMEs with various types of productss produced, including culinary to handycraft. The problem faced by this association is that their business has not developed since at was pioneered until now. This is due to the lack of understanding of entrepreurship and the lack of entrepreneurial spirit. The purpose of Community Service is to provide knowledge about entrepreneurship and motivate MSMEs to be more enthusiastic in running their businesses. The method of implementing community service activities is the lecture and discussion method. Meamwhile, the implementation of community service activities in March – May 2024. After the counseling was carried out, there was an increase in knowledge and understanding of entrepreneurship among the participants, understanding and understanding the success factors of a business and there was a positive change in behavior, namely being more enthusiastic in entrepreneurship. Keywords: Entrepreneurship, Motivation, Counselling, Skills technology